2018
DOI: 10.1080/07380577.2017.1422607
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Difficulties Scale (CDS): Translation and Psychometric Evaluation Among Iranian Mothers of Cerebral Palsy Children

Abstract: The aim of this study was to investigate of psychometric properties of the Caregiver Difficulties Scale (CDS) for Iranian caregivers of children with cerebral palsy (CP). After a forward-backward translation, the Persian version of CDS (P-CDS) was administered to 151 Iranian mothers of CP children. The confirmatory factor analysis (CFA) was applied to measure the factor structure of P-CDS. The reliability was evaluated by examining internal consistency and test-retest method over a 2-week period using Cronbach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 23 publications
6
35
0
Order By: Relevance
“…Notably, despite the working age of these caregivers, most of the sample was unemployed, and most were female housewives . Evaluating the QoL of parents of disabled individuals, it was observed that only one of the spouses was employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, despite the working age of these caregivers, most of the sample was unemployed, and most were female housewives . Evaluating the QoL of parents of disabled individuals, it was observed that only one of the spouses was employed.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The correlation matrix between the ZBI scale and the WHOQOL-BREF instrument showed that the presence of burden negatively influenced all WHOQOL-BREF domains, which indicates that the individuals most burdened by the care task present decrease subjective perception of their QoL. 20 Studies with caregivers not only of children but also of adults with intellectual disabilities 27 and with physical disabilities 31 also found an inverse proportional statistical significance between QoL and level of burden, so that the role of providing care leads to burden and negatively affects the QoL of caregivers.…”
Section: F I G U R E 1 Box-plot Graphs Of the Zarit Burden Interview mentioning
confidence: 99%
“…When the amount of the burden and difficulties of caregiving increases, mothers feel hopeless and as a result their QoL decreases significantly (Farajzadeh et al, 2018; Garip et al, 2017). Some of the studies found that providing care for a child with functional limitations and long-term dependence influenced mothers’ QoL (Garip et al, 2017; Khayatzadeh et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Many children with CP may have limitations in self-care functions such as feeding, bathing, dressing, grooming, ambulation and experience communicative, sensory and intellectual impairments (Svedberg et al, 2010; Tseng et al, 2016). The most children with CP are cared for by their mothers who are primary caregivers in developing countries such as Turkey (Farajzadeh et al, 2018; Garip et al, 2017). Caregiving covers a very wide range of activities such as heavy lifting and turning, bathing, helping the child to use the toilet, getting the child to sleep, dressing and assisting the transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Higher scores indicate higher caregiver's difficulties. This tool has sufficient validity and reliability among Iranian mothers of children with CP [21].…”
Section: Outcome Measures D Caregiver Difficulties Scale (Cds)mentioning
confidence: 94%